Systemic versus local injection of bone marrow mesenchymal stem cells on 5-fluorouracil treated parotid glands of albino rats - Massieh, Caroline; A. El-Zainy, Medhat; Magdy Amin, Reham; Fathy, Iman (Brazilian Dental Science, 2021)
Objective: Head and neck cancer is the sixth leading cancer by incidence worldwide and eighth by death. Recent reports revealed that, not only radiotherapy but also chemotherapy may induce xerostomia. The aim of this study was to compare the possible regenerative effect of BMSCs through systemic and local injections. Material and Methods: 52 male Albino rats were randomly divided into 4 groups: Group 1: 10 rats received 0.5 ml of PBS by injection. Group 2: 14 rats received an intraperitoneal injection of 5-FU drug. Group 3: 14 rats were injected the same dose of 5-FU then received an intraglandular transplantation of BMSCs suspended in 0.5 ml of PBS at day 1 after 5-FU administration. Group 4: 14 rats were injected the same dose of 5-FU then received an intravenous injection of BMSCs suspended in 0.5 ml of PBS via the tail vein at day 1 after 5-FU administration. Results: Histological examination showed that group 2 showed features of severe degenerative changes which increased over time. Group 3 showed increasing amelioration in the ductal structure overtime. Group 4 also showed regenerated ductal elements however concerning apoptotic changes, immunohistochemistry results revealed improvement in both group 3 and 4 over group 2 with no statistical difference between groups 3 and 4. Conclusion: Histological and immunohistochemical features in group 3 and group 4 revealed similar amelioration in regenerative potentials. On the other hand, regenerative features of both experimental groups were statistically significant as compared independently to group 1. KEYWORDS 5-fluourouracil; anti-caspase-3; BMSCs; H&E; parotid salivary gland.